Properties and Optimum Percentage of Concrete Containing Expanded Polystyrene (EPS) and Palm Oil Fuel Ash (POFA) as Replacement Materials - Kamarudin, Putri Iwana; Abdullah, Mohd. Sufyan; Osman, Mohamad Hairi (Progress in Engineering Application and Technology, 2022)
Concrete is one of the effective and widely used developments materials in any construction all around the world and will continue as the dominant construction along with the growth of human civilization and the development of countries. This development can cause high demand for natural resources such as aggregate and also cement. Thus, the aim of this research is to determine the properties and optimum percentage of concrete when aggregate and cement content were replaced with Expanded Polystyrene (EPS) and Palm Oil Fuel Ash (POFA). Five (5) testing were used in this research which are XRD test, slump test, density test, water absorption test and compressive strength test. XRD test was used to compare the chemical composition of POFA and cement. Another four (4) testing were conducted to identify the mechanical and physical properties of concrete containing EPS and POFA. The DOE method was used to prepare concrete mixtures with varying proportions of EPS and POFA replacement. The result shows that specimens’ average compressive strength increase with the increase of the specimens’ age. Moreover, as the amount of EPS and POFA in the concrete mixture increased, the slump, density and compressive strength decreased. However, water absorption increased as the POFA and EPS contents increased. In conclusion, the optimum percentage of EPS and POFA replacements can be replaced up to 10% respectively, and EPS and POFA can be used as replacement materials in concrete.